Žirgų kapai Rytų Lietuvos pilkapynuose vėlyvajame geležies amžiuje (IX-XII a.) - Juškaitis, Vytautas (Archaeologia Lituana, 2005)
East Lithuanian barrows spread out in the Eastern Lithuanian area and northwestern part of Belarus. Horse burials are quite often found during archeological excavations of East Lithuanian barrows. But there is no thorough summary data on the research material. This article deals only with the horse burials of East Lithuanian barrows of the Late Iron Age. The purpose of the article is to summarize the funeral customs of horse graves, to define the chronology of horse burials, to mark grave types according to funeral customs, to define the origin of the custom to bury horses, to mark the regions according La horse burial customs. 10 restore the ritual of burying a horse according to archeological data.Information about horse graves in East Lithuanian harrows comes from the middle of the 19th century. In the second half of the 19th century barrows were excavated by A. Pliateris, A. H. Kirkoras, but most of all horse burials in the end of the 19th century were examined by F. Pokrovskis. In the interwar time, a lot of horse graves were explored by Polish archeologists R. Jakimowicz, E. and W. Holubovicz. From the middle of the 19th till the middle of the 20th century the material was only accumulated and published. There is no summary on horse graves.A lot of horse graves in the East Lithuanian barrow cemeteries were analyzed in the 60ies (Bildos, Darsūniškis, Didžiuliai, Dieveniškės, Kapitoniškės, Katkuškės, Kunigiškės). Most barrows with horse graves were explored by A. Tautavičius. The material of the excavations was published in the MADA, ILKI editions. From the 60ies till now, almost every year horse graves are found.Overall, 74 barrow cemeteries are known, in which horse graves or outfit are found. 48 barrows cemeteries were explored by archeologists who found 153 horse graves (Fig. 1).For the first time the research data were more properly summarized in the hook “The Horse of Lithuanian Warrior” written by R. Volkaitė-Kulikauskienė. In 1992 was published the article “The barrows of Alinka (Raistinė)”, written by A. Bliujienė. In this article the author discusses not only the funeral customs of the Alinka barrow cemetery. but also defines the evolution and chronology of harrows with horse graves. Empty burials are all ached by her to symbolical horse burials.In total, there were explored 21 East Lithuanian barrow cemeteries, in which 47 horse inhumations were found. Most of these harrow cemeteries spread out to the north from the Neris River. Only few of them are on the left side of the river (Fig. 2).The orientation of 30 horses was defined. Figure 2 shows, that the custom to bury a horse with the head to the west or northwest dominated only in the western part of East Lithuanian harrow cemeteries. In 90 percent of the horses in the western part, the head was oriented 10 the west and northwest. In the other East Lithuanian barrow cemeteries, horses were buried in all directions almost equally. Most likely the western part was influenced by the tribe of upland Lithuanians who also buried horses their heads to the west.No barrow inside a stone circle contained horse inhumations. Most often the burial items of horse inhumations are a riding bit and a sickle.Horse cremations, as compared with inhumations, spread out more to the south. Overall, 30 barrow cemeteries are known, in which 71 horse cremations were found. There are known five barrows inside stone circles with a horse cremation found in them (Fig. 4).There are known seven cases when in the same barrow also humans were buried. Most often the burial items of horse cremations are a riding bit and a sickle.We give symbolical name to such horse burials, in which there are only horse outfit, but no bones. Before writing about symbolical horse burials, it should be mentioned that a sickle also symbolizes horse burial. There is an opinion that also empty barrows should be ascribed to symbolical horse graves (Bliujienė, 1992, p. 120). The spread of symbolical horse graves almost coincides with the spread of horse cremations. Overall. 19 barrow cemeteries are known, in which 38 symbolical horse graves were found. The largest number of symbolical horse burials was found in Alinka (8). Pabarė (6), Kapitoniškės (3). In other places 1-2 symbolical horse burials were found. Most often the burial items of a symbolical grave are a sickle and a riding bit.During archeological excavations there were found 310 grave items, among them 88 bridle bits, 72 sickles, 40 bridle jingles, 34 stirrups, 34 belt buckles, 15 riveted bridles, 8 spirals, 7 horse collar bells, 4 iron loops, 4 saddle spangles, 2 whipstocks, penannulars with cylindrical terminals.There is an opinion that if a horse burial is found in a harrow with moats and without grave inside stone circles, this grave should be ascribed to the 9th-12th centuries (Kuncienė, 1969, p. 57: Bliujienė, 1992, p. 105). A Bliujienė defines the following of development of horse burials: inhumation ? cremation ? horse outfit without hones ? sickle ? empty barrow (Bliujienė, 1992, p. 124). To prove this statement, she indicates a more intensive pressure from the neighbours in 9th-12th centuries. This means that more horses were needed to defend the native land (Bliujienė, 1992, p. 121). But it is possible lo form also another sequence of development or horse burials. At first, the earliest horse burials should he not inhumations hut cremations, because they arc found in the harrows inside stone circles. An evidence that horse cremation upsprang before inhumations is a horse cremation found in the harrow of Katkuškės No. 1 b. There was found a fibula together with other common grave items. The archeologist O. Kuncienė dates this harrow to the 10th-12th century. This date could he questioned, after all penannular with cylindrical terminals came lip in the 8th century and were most widely used in the 9th-10th centuries. The sickle found in this grave is typical of the end of the first millennium. That is why this horse grave should be dated to the 8th-10th centuries. In the horse cremation of Kretuonys barrow No 54, there was found a sickle typical of the 5th-7th centuries. But such sickles were used only till the 10th century. Therefore, the barrow of Kretuonys, No 54 should he dated to the end of the first millenium. Meanwhile no any barrow in which horse inhumations or cremations were found had graves inside stone circles. These barrows most often were circled by continuous moats. Ibis fact shows that these barrows arc younger.From all these facts it is possible to deduce that, cremation came up first, and only from the beginning of the 2nd millennium inhumation and symbolical horse graves appeared. But although inhumations and symbolical graves came up, cremations didn’t disappear, either.All three ways of burial existed together. Thereby, horse cremation is dated to the 8th-12th centuries and inhumation and symbolical graves to the 10th-12th centuries.According to the spread of harrows inside the stone circles in which horse graves were found, it is supposed that the rite of burning a horse could come up firstly in the contermporary districts of Šalčininkai and Vilnius aproximately in the 9th century. The earliest horse cremations were found here (Fig. 4). From here this rite could spread out to the north of the Žeimena river, to the east and west of the Neris river. Horse inhumations most likely appeared in the western part of East Lithuanian barrow cemeteries approximately in the 10th century.In the western part of East Lithuanian barrow cemeteries, horses most often were oriented their head to the west or northwest, the same as in Upland Lithuania. That shows that this rite could come from the territory of Upland Lithuania. When horse inhumations spread to the east, their funeral customs changed. It was already no matter, to which side a horse was oriented. By the way, the rite to bury a not burnt horse didn’t spread all over the territory of East Lithuanian barrow cemeteries: so far, no horse inhumations have been found in the upper Merkys, although barrow cemeteries are rather thoroughly explored here.In the western part of East Lithuanian harrow cemeteries, digging a pit for a horse followed the west-cast or northwest-southeast direction. A horse was buried with its outfit. Sometimes it was very richly decorated. The richest horse graves are known from the barrows of Alinka No 4, Lapušiškė No 4. But most often horses are buryied with a modest outfit.According to the horse funeral customs, the East Lithuanian barrow cemeteries belong to four regions (Fig. 6). These regions most likely could be related with the borders of lands. Deltuva could be related with the northern region of East Lithuanian harrow cemeteries, Lietuva with the western and Nalšia with the eastern one. The Southern region is most often attached to Lithuania. though it might be a separate land in the 9th-12th centuries, because here the horse funeral customs differ from those of other regions.But horse graves alone are not enough to define the borders of the lands in the 9th-12th centuries. Defining the borders of the lands in the East Lithuanian barrow cemeteries, funeral customs of humans should be explored using data of hill-forts. settlements, written sources. Horse graves should be only one of the criteria.